Infantile-Onset Disorders of Mitochondrial Replication and Protein Synthesis - Nogueira, Célia (2012)
Most inherited mitochondrial diseases in infants result from mutations in nuclear genes encoding proteins with specific functions targeted to the mitochondria rather than primary mutations in the mitochondrial DNA (mtDNA) itself. In the past decade, a growing number of syndromes associated with dysfunction resulting from tissue-specific depletion of mtDNA have been reported in infants. MtDNA depletion syndrome is transmitted as an autosomal recessive trait and causes respiratory chain dysfunction with prominent neurological, muscular, and hepatic involvement. Mendelian diseases characterized by defective mitochondrial protein synthesis and combined respiratory chain defects have also been described in infants and are associated with mutations in nuclear genes that encode components of the translational machinery. In the present work, we reviewed current knowledge of clinical phenotypes, their relative frequency, spectrum of mutations, and possible pathogenic mechanisms responsible for infantile disorders of oxidative metabolism involved in correct mtDNA maintenance and protein production.